The Effect of Lumbar Support on Lower Back Pain in Ojek Online Drivers in Solo Indonesia - Rachmat, Nur; Zubaidi, Alfan (Advances in Social Sciences Research Journal, 2020)
Online motorcycle taxi drivers (Ojek Online) work long hours driving motorbikes. the driver experiences low back pain. The use of elastic lumbar support when driving is expected to reduce pain when sitting too long in a two-wheeled vehicle and when lifting weights. Therefore, the authors are interested in conducting research on the effect of use of lumbar support on lower back pain in ojek online drivers.. This type of qualitative research is quasi-experimental with one group pretest-posttest design test approach. This research will be conducted at the online motorcyclist basecamp of Solo, Central Java, Indonesia in February to March 2020. The sample used in this study is 80 people with back discomfort due to pain when sitting while riding a two-wheeled vehicle on a motorcycle taxi driver online that fulfills inclusion and exclusion. The measurement tool used is Visual Analog Scale. Normality test data used Normality test using Kolmogorov-Smirnov. Hypothesis testing in this study uses Wilcoxon on the value of the degree of pain at the beginning and at the end of the study. The results of the study are that there is an influence of the use of lumbar corset on online back pain of motorcycle taxi drivers online. There is a decrease in low back pain to the online motorbike driver after being treated with elastic lumbar support